From Bauhaus to ecohouse a history of ecological design - Anker, Peder. (Louisiana State University Press, 2010)
Global warming and concerns about sustainability recently have pushed ecological design to the forefront of architectural study and debate. As Peder Anker explains in From Bauhaus to Ecohouse, despite claims of novelty, debates about environmentally sensitive architecture have been ongoing for nearly a century. By exploring key moments of inspiration between designers and ecologists from the Bauhaus projects of the interwar period to the eco-arks of the 1980s, Anker traces the historical intersection of architecture and ecological science and assesses how both remain intertwined philosophicall.